Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat pada Pasien Hipertensi di Puskesmas Karangsembung - Novan Ibrahim; Sri Marfuati; Nanang Ruhyana (Universitas Pahlawan Tuanku Tambusai, 2026)
Hypertension is a non-communicable disease requiring long-term treatment and is one of the leading causes of cardiovascular complications. Adherence to antihypertensive medication is essential to maintain stable blood pressure and prevent complications. One of the factors influencing medication adherence is family support. This study aimed to determine the relationship between family support and medication adherence among hypertensive patients at Karangsembung Health Center, Cirebon Regency, in 2024. This study used an analytic observational design with a cross-sectional approach. The population consisted of hypertensive patients in the working area of Karangsembung Health Center, with a sample of 96 respondents selected using consecutive sampling technique. The independent variable was family support, while the dependent variable was medication adherence. Data were collected using a family support questionnaire, the Morisky Medication Adherence Scale (MMAS), and medical records. Data analysis was performed using the Spearman Rank correlation test. The results showed that most respondents had good family support, namely 63 respondents (65.6%), and the majority were adherent to medication, namely 73 respondents (76.0%). The Spearman Rank test showed a p-value of 0.000 (≤0.05) with a correlation coefficient of 0.550, indicating a positive relationship with moderate correlation strength. In conclusion, there is a significant relationship between family support and medication adherence among hypertensive patients at Karangsembung Health Center, where better family support is associated with higher medication adherence.